Sustainable Ecotourism Supply Chain Development - Fitnantyo Bimawan; Abdul Malik; Lis Widowati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Ecotourism is an important sector in the rapidly growing tourism industry, allowing tourists to enjoy natural and cultural beauty while preserving the environment. Developing a sustainable ecotourism supply chain is a key aspect in ensuring that ecotourism can continue without damaging the environment and culture that is its attraction. This research aims to reveal the main principles in developing a sustainable ecotourism supply chain, by considering several aspects. This research method uses a qualitative study, which focuses on understanding the target aspects using literature analysis and observation techniques. The research results show that close collaboration between the parties involved is essential in developing a sustainable ecotourism supply chain. The government has an important role in formulating policies and regulations that support sustainability principles. Tourism entrepreneurs need to adopt environmentally friendly practices, market ecotourism responsibly, and provide economic benefits to local communities. Education is needed for sustainable development of all stakeholders and long-term commitment to sustainability principles.